Development and Characterization of Solution‐Processable Dithieno[3, 2‐b : 2', 3'‐d]thiophenes Derivatives with Various End‐capped Groups for Organic Field‐Effect Transistors. Issue 10 (5th October 2022) - Kang, Hyunwoo; Jang, Yuhyeon; Ho, Dongil; Ryu, Soomin; Kim, Choongik; Seo, SungYong
Abstract: In this paper, four organic materials based on dithieno[3, 2‐b : 2', 3'‐d]thiophene (DTT) core structure with end‐capping groups (phenyl and thienyl) and linker (acetylenic and olefinic) between DTT‐core and end‐capping groups were synthesized and characterized as solution‐processable organic semiconductors (OSCs) for organic field‐effect transistors (OFETs). Thermal, optical, and electrochemical properties of the corresponding materials were determined. Next, all DTT‐derivatives were coated by solution‐shearing method, and the thin‐film microstructures and morphologies were investigated. To investigate the electrical performance of four newly synthesized DTT‐derivatives, bottom‐gate/top‐contact OFETs were fabricated and characterized in ambient condition. It was found that substitution of acetylenic for olefinic linkers between DTT‐cores and end‐capping groups enhanced device performance. Especially, the resulting OFETs based on the compound containing phenylacetylene exhibited the highest hole mobility of 0.15 cm 2 /Vs and current on/off ratio of ∼10 6, consistent with film morphology and texture showing long range interconnected crystalline grains and strong diffraction peaks. Abstract : New dithieno[3, 2‐ b  : 2', 3'‐ d ]thiophene‐based small‐molecule organic semiconductors with various end‐capping groups were synthesized and employed as active layers in organic field‐effect transistors. Organic compounds with acetylenic linkage exhibited superior electrical performance with about 360 times larger mobility than those with olefinic linkage.